DÁWLETYARBEK DÁSTANINIŃ QARAJAN BAQSI KABULOV VARIANTI HAQQINDA - Esemuratova, U.X. (SCIENCE and SOCIETY, 2023)
The article discusses the version of the Karakalpak folk epic Davlatyorbek's Karajan Bakhshi. The difference between this option and other options is organized in a comparative way. The plot of Karazhan Bakhsh, the skills in narration and artistic development are shown. The individual talent of Karazhan Bakhshi in describing the events of the epic is studied. Bakhshi explained the unique feature of the variant.